Feasibility of a drug allergy registry-based excipient allergy database and call for universal mandatory drug ingredient disclosure: the case of PEG - Kan, Andy Ka Chun; Chiang, Valerie; Saha, Chinmoy; Au, Elaine Y. L.; Li, Philip Hei (Frontiers in Allergy, 2024)
Background Excipient allergy is a rare, but potentially lethal, form of drug allergy. Diagnosing excipient allergy remains difficult in regions without mandatory drug ingredient disclosure and is a significant barrier to drug safety. Objective To investigate the feasibility of a drug allergy registry-based excipient database to identify potential excipient culprits in patients with history of drug allergy, using polyethylene glycol (PEG) as an example. Methods An excipient registry was created by compiling the excipient lists pertaining to all available formulations of the top 50 most reported drug allergy culprits in Hong Kong. Availability of excipient information, and its relationship with total number of formulations of individual drugs were analysed. All formulations were checked for the presence or absence of PEG. Results Complete excipient information was available for 36.5% (729/2,000) of all formulations of the top 50 reported drug allergy culprits in Hong Kong. The number of formulations for each drug was associated with proportion of available excipient information (ρ = 0.466, p = 0.001). Out of 729 formulations, 109 (15.0%) and 620 (85.0%) were confirmed to contain and not contain PEG, respectively. Excipient information was not available for the other 1,271 (63.6%) formulations. We were unable to confirm the presence or absence of PEG in any of the top 50 drug allergy culprits in Hong Kong. Conclusion In countries without mandatory drug ingredient disclosure, excipient databases are unlikely able to identify potential excipient allergy in drug allergy patients. Legislations to enforce mandatory and universal ingredient disclosure are urgently needed.